Предмет: Математика,
автор: burejkee
(x-3)(x+2)-(x-1)(x+1)=3x+7
Ответы
Автор ответа:
0
1)(x-3)(x+2)=x2-6
2)(x-1)(x+1)=x2+1
3)x2-6-x2+1=3x+7(икс в квадрате сокращаются)
4)-6+1=3х+7(теперь цифры с цыфрами,буквы с буквами)
5)-3х=7+6-1
6)-3х=12
7)х=12/(-3)
8)х=-4
Ответ:-4
2)(x-1)(x+1)=x2+1
3)x2-6-x2+1=3x+7(икс в квадрате сокращаются)
4)-6+1=3х+7(теперь цифры с цыфрами,буквы с буквами)
5)-3х=7+6-1
6)-3х=12
7)х=12/(-3)
8)х=-4
Ответ:-4
Автор ответа:
0
не правильно
Автор ответа:
0
Почему?
Автор ответа:
0
Обьясните почему!
Похожие вопросы
Предмет: Математика,
автор: valentinamirol
Предмет: Английский язык,
автор: dmitrijkosatyj
Предмет: Физика,
автор: CamillaArlert
Предмет: Физика,
автор: olenikapersik